Principles and Practice of Pediatric Oncology. - Pizzo, Philip A.; Poplack, David G. (Philadelphia : Wolters Kluwer Health, 2010)
Thoroughly updated for its Sixth Edition,Principles and Practice of Pediatric Oncologyprovides a comprehensive review of the multiple disciplines that make up the care and research agendas for children with cancer. It is the most comprehensive textbook of pediatric oncology ever put together, covering biology and genetics and detailing the diagnosis, multimodal treatment, and long-term management of patients with cancer. The fundamental principles of supportive care and the psychosocial aspects of support for patients and families are also discussed. Twenty percent of the chapters in this edition are either brand-new or written by new contributors, and all the other chapters have been considerably updated. The book provides state-of-the-art information on the molecular genetics and biology of cancer as well as new approaches to diagnosis and management. A companion website offers the fully searchable text.
CHAPTER 26A GLIOMAS, EPENDYMOMAS, AND OTHER NONEMBRYONAL TUMORS OF THE CENTRAL NERVOUS SYSTEM -- CHAPTER 26B EMBRYONAL AND PINEAL REGION TUMORS -- CHAPTER 27 RETINOBLASTOMA -- CHAPTER 28 PEDIATRIC LIVER TUMORS -- CHAPTER 29 RENAL TUMORS -- CHAPTER 30 NEUROBLASTOMA -- CHAPTER 31 RHABDOMYOSARCOMA -- CHAPTER 32 THE NONRHABDOMYOSARCOMA SOFT TISSUE SARCOMAS -- CHAPTER 33 EWING SARCOMA -- CHAPTER 34 OSTEOSARCOMA: BIOLOGY, DIAGNOSIS, TREATMENT, AND REMAINING CHALLENGES -- CHAPTER 35 GERM CELL TUMORS -- CHAPTER 36 ENDOCRINE TUMORS -- CHAPTER 37 MANAGEMENT OF INFREQUENT CANCERS OF CHILDHOOD -- SECTION 5 SUPPORTIVE CARE OF CHILDREN WITH CANCER -- CHAPTER 38 ONCOLOGIC EMERGENCIES -- CHAPTER 39 HEMATOLOGIC SUPPORTIVE CARE FOR CHILDREN WITH CANCER -- CHAPTER 40 INFECTIOUS COMPLICATIONS IN PEDIATRIC CANCER PATIENTS -- CHAPTER 41 NUTRITIONAL SUPPORTIVE CARE -- CHAPTER 42 PAIN AND SYMPTOM MANAGEMENT -- CHAPTER 43 NURSING SUPPORT OF THE CHILD WITH CANCER -- CHAPTER 44 REHABILITATION OF THE CHILD WITH CANCER -- CHAPTER 45 PSYCHIATRIC AND PSYCHOSOCIAL SUPPORT FOR THE CHILD AND FAMILY -- CHAPTER 46 ETHICAL CONSIDERATIONS IN PEDIATRIC ONCOLOGY -- SECTION 6 OTHER ISSUES ARISING AT DIAGNOSIS, DURING TREATMENT, AND AFTER CESSATION OF THERAPY -- CHAPTER 47 LATE EFFECTS OF CHILDHOOD CANCER AND ITS TREATMENT -- CHAPTER 48 EDUCATIONAL ISSUES FOR CHILDREN WITH CANCER -- CHAPTER 49 PALLIATIVE CARE FOR THE CHILD WITH CANCER -- CHAPTER 50 ECONOMIC ISSUES IN PEDIATRIC CANCER -- CHAPTER 51 PEDIATRIC CANCER: ADVOCACY, INSURANCE, EDUCATION, AND EMPLOYMENT -- CHAPTER 52 COMPLEMENTARY AND ALTERNATIVE MEDICAL THERAPIES IN PEDIATRIC ONCOLOGY -- CHAPTER 53 PEDIATRIC ONCOLOGY IN COUNTRIES WITH LIMITED RESOURCES -- CHAPTER 54 PREVENTING CANCER IN ADULTHOOD: ADVICE FOR THE PEDIATRICIAN -- CHAPTER 55 RESOURCES FOR CHILDREN WITH CANCER, THEIR FAMILIES, AND PHYSICIANS -- INDEX.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Cancer in children; Electronic books